The Development of Bolokuncoro Interactive Learning Multimedia for Language Literacy of Children Aged 5-6 Years Old (Universitas Negeri Semarang, 2020)
The objectives of this research are to develop Bolokuncoro interactive learning multimedia for language literacy of children aged 5-6 years old at the Pembina Public Kindergarten Jebres Solo, and to find out the effectiveness of interactive learning Bolokuncoro multimedia for language literacy for children aged 5-6 years at the Pembina Public Kindergarten Jebres Solo. This research is a Research and Development (R&D) model with ADDIE employing experimental and control classes as sample design. Bolokuncoro interactive learning multimedia integrates the local wisdom of Solo into the learning theme and is added with educational games. The results of this study are the production of interactive learning learning Bolokuncoro multimedia, interactive learning interactive learning Bolokuncoro is effective for language literacy of children aged 5-6 years old in the Pembina Public Kindergarten Jebres Solo with the results of the n-gain of the experimental class score is 0.84 which belongs to the high category and the n-gain of the control class is 0.51 which belongs to medium category.